Single-payer or a multipayer health system: a systematic literature review. (October 2018) - Petrou, P.; Samoutis, G.; Lionis, C.
Abstract: Objectives: Healthcare systems worldwide are actively exploring new approaches for cost containment and efficient use of resources. Currently, in a number of countries, the critical decision to introduce a single-payer over a multipayer healthcare system poses significant challenges. Consequently, we have systematically explored the current scientific evidence about the impact of single-payer and multipayer health systems on the areas of equity, efficiency and quality of health care, fund collection negotiation, contracting and budgeting health expenditure and social solidarity. Study design: This is a systematic review based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Methods: A search for relevant articles published in English was performed in March 2015 through the following databases: Excerpta Medica Databases, Cumulative Index of Nursing and Allied Health Literature, Medical Literature Analysis and Retrieval System Online through PubMed and Ovid, Health Technology Assessment Database, Cochrane database and WHO publications. We also searched for further articles cited by eligible papers. Results: A total of 49 studies were included in the analysis; 34 studied clinical outcomes of patients enrolled in different health insurances, while 15 provided a qualitative assessment in this field. Conclusion: The single-payer system performs better in terms of healthcare equity, risk pooling and negotiation, whereas multipayer systems yield additional options to patients and are harder to be exploited by the government. A multipayer system also involves a higher administrative cost. The findings pertaining to the impact on efficiency and quality are rather tentative because of methodological limitations of available studies. Highlights: Universal healthcare coverage is 'the most powerful concept that public health has to offer'. Selection of the payer type should be country specific and a context-sensitive process. Single-payer system promotes equity, while multipayer system may be superior in efficiency enhancement. Multipayer system carries higher running costs, while a single-payer system may be exploited under a hostile government. No differences in quality of care were identified between the two types.